2018
DOI: 10.1038/s41467-018-03749-0
|View full text |Cite
|
Sign up to set email alerts
|

Human single neuron activity precedes emergence of conscious perception

Abstract: Identifying the neuronal basis of spontaneous changes in conscious experience in the absence of changes in the external environment is a major challenge. Binocular rivalry, in which two stationary monocular images lead to continuously changing perception, provides a unique opportunity to address this issue. We studied the activity of human single neurons in the medial temporal and frontal lobes while patients were engaged in binocular rivalry. Here we report that internal changes in the content of perception a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 79 publications
4
46
0
1
Order By: Relevance
“…Therefore, the PFC appears to have a centrally important role in the emergence of conscious perception. Previous electrophysiological studies in the PFC have revealed representations of the content of consciousness using exogenous perceptual manipulations (23,34) and preparatory activity before spontaneous perceptual changes, that could not however be dissociated from signals related to voluntary motor reports (24,35). Furthermore, studies using BOLD fMRI that indirectly reflects neural activity disagree on the impact of voluntary reports on PFC activity during spontaneous perceptual transitions (12,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the PFC appears to have a centrally important role in the emergence of conscious perception. Previous electrophysiological studies in the PFC have revealed representations of the content of consciousness using exogenous perceptual manipulations (23,34) and preparatory activity before spontaneous perceptual changes, that could not however be dissociated from signals related to voluntary motor reports (24,35). Furthermore, studies using BOLD fMRI that indirectly reflects neural activity disagree on the impact of voluntary reports on PFC activity during spontaneous perceptual transitions (12,19).…”
Section: Discussionmentioning
confidence: 99%
“…The spatiotemporal build-up of 1-9 Hz bursts before spontaneous perceptual transitions is reminiscent of the Readiness Potential or Bereitschaftspotential; i.e., a steady accumulation of activity in the Anterior Cingulate Cortex (ACC) and Supplementary Motor Area (SMA) preceding the awareness of the volition to initiate a report (36)(37)(38)(39). This motor-related process is reflected in a spiking activity build-up before the voluntary motor report of a perceptual transition in BR (24). Our results show that both linear and non-linear increases in the instantaneous amplitude and spatial-spread of low-frequency prefrontal bursts respectively precede spontaneous transitions 19 | Page in the content of consciousness without voluntary behavioural reports.…”
Section: Discussionmentioning
confidence: 99%
“…When paired with electrophysiological investigations of the non human primate visual system (57,58), BR has revealed that the proportion of feature selective neurons reliably reflecting conscious content increases as one progresses in the visual cortical hierarchy from early visual areas (48,59,60) to later temporal regions (20,21,50). Recent single unit recordings in human medial frontal and anterior cingulate cortex areas during BR found non-selective modulation of neural activity before spontaneous perceptual transitions, suggesting that some frontal cortical areas might reflect the prerequisites of conscious perception than conscious content per se (22). In contrast, our results demonstrate conscious content representations in a subregion of the macaque lateral PFC, where cells are selective for faces, complex visual objects and direction of motion (45-47, 61, 62) and reciprocally connected with the inferotemporal cortex (63).…”
Section: Br Offers a Distinct Advantage Over Other Paradigms Of Visuamentioning
confidence: 99%
“…In contrast, our results demonstrate conscious content representations in a subregion of the macaque lateral PFC, where cells are selective for faces, complex visual objects and direction of motion (45-47, 61, 62) and reciprocally connected with the inferotemporal cortex (63). Importantly, previous electrophysiological studies in the PFC during conscious perception either utilized a motor report (19,21,22,64), and were therefore conflated by consequences of conscious perception, or investigated perceptual modulation among neurons selective to faces and complex objects with a no-report BFS paradigm. In BFS, perceptual dominance and suppression are externally induced due to an abrupt and strong change in the feedforward input and not endogenously driven as in BR, wherein neural activity modulations could contribute causally towards changes in conscious perception (20).…”
Section: Br Offers a Distinct Advantage Over Other Paradigms Of Visuamentioning
confidence: 99%
See 1 more Smart Citation